Early Medieval Archaeological Landscape of Assam (AD 600–AD 1200): Preliminary Survey in Western Assam, District Goalpara. (17th May 2017) - Barman, Bratatee
A large number of religious monuments from this period are spread across the state (Choudhury 2013 ). However, nothing is known of firstly, the neighbouring habitation sites. Secondly, the regional network of such sites. Much of the archaeological research in Assam is mainly single-site oriented, and art historical methods are often used for to study such sites. As a result the early medieval structures or monuments remain isolated features in the landscape sans context in regards to its immediate surroundings. Documentation of more settlements of this period and studying their characteristics and their connection to other neighbouring sites is the key to comprehensively understanding the early medieval history of Assam. Having felt such a need, this small scale, independent, surface survey project was carried out across nine modern villages around the archaeological site of Sri Surya Pahar (SSP) in Goalpara district, western Assam. The main aim of this project was to explore the immediate surroundings of Sri Surya Pahar site (SSP site) and document the visible archaeological features and examine the potential of this area for future projects.